2017
DOI: 10.33549/physiolres.933374
|View full text |Cite
|
Sign up to set email alerts
|

The In Vivo Effects of Adenine-Induced Chronic Kidney Disease on Some Renal and Hepatic Function and CYP450 Metabolizing Enzymes

Abstract: Adenine-induced model of chronic kidney disease (CKD) is a widely used model especially in studies testing novel nephroprotective agents. We investigated the effects of adenine-induced CKD in rats on the activities of some xenobiotic metabolizing enzymes in liver and kidneys, and on some in vivo indicators of drug metabolism (viz pentobarbitone sleeping time, and plasma concentration of theophylline 90 min post administration). CKD was induced by orally feeding adenine (0.25 % w/w) for 35 days. Adenine induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…In addition, a recent study investigated the effects of adenine-induced chronic kidney disease (CKD) in rats on the activities of some XMEs in liver and kidneys. It was found that the plasma theophylline concentration was significantly increased in rats with CKD 206 . Moreover, a reduced metabolism of midazolam could be observed in rats with acute kidney injury (AKI) 207 .…”
Section: Disease–drug Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study investigated the effects of adenine-induced chronic kidney disease (CKD) in rats on the activities of some XMEs in liver and kidneys. It was found that the plasma theophylline concentration was significantly increased in rats with CKD 206 . Moreover, a reduced metabolism of midazolam could be observed in rats with acute kidney injury (AKI) 207 .…”
Section: Disease–drug Interactionsmentioning
confidence: 99%
“…Among them, the effects of polymicrobial sepsis on the activity and gene expression of hepatic microsomal CYP450 have attracted considerable attention due to their potential disease–drug interactions in clinical therapy. It has been reported that the major hepatic CYP isoforms CYP1A1, 1A2, 2B1, 2E1 were down-regulated during polymicrobial sepsis 208 , 203, 204, 205, 206, 207, 208, 209, 210, 211, 212, 213, 214, 215, 216, 217, 218, 219, 220, 221, 222, 223, 224. Moreover, results from mechanistic studies show that nitric oxide (NO) and the AhR play key potential roles in down-regulation of hepatic CYP during sepsis 225 , 226 .…”
Section: Disease–drug Interactionsmentioning
confidence: 99%
“…Our results support findings from other studies showing a lack of adenine hepatotoxicity ( 42 , 43 ). However, another study reported a hepatotoxic effect of adenine as demonstrated by elevated liver enzymes in response to inflammation ( 44 ). This is in contrast with the results of our study, in which increased systemic inflammation was not associated with elevated liver enzymes in adenine-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2S1 was recently discovered, and it is expressed in the skin and the small intestines. This enzyme is involved in all-transretinoic acid metabolism into the skin [141,142]. There is no information about its expression in patients with CKD.…”
Section: Alterations Of Drug Metabolism During Chronic Kidney Diseasementioning
confidence: 99%